2013
DOI: 10.1371/journal.pone.0058140
|View full text |Cite
|
Sign up to set email alerts
|

Early Differentiated CD138highMHCII+IgG+ Plasma Cells Express CXCR3 and Localize into Inflamed Kidneys of Lupus Mice

Abstract: Humoral responses are central to the development of chronic autoimmune diseases such as systemic lupus erythematosus. Indeed, autoantibody deposition is responsible for tissue damage, the kidneys being one of the main target organs. As the source of pathogenic antibodies, plasma cells are therefore critical players in this harmful scenario, both at systemic and local levels. The aim of the present study was to analyze plasma cells in NZB/W lupus mice and to get a better understanding of the mechanisms underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…þ PCs have also been described in autoimmunity, where they serve to exacerbate rather than suppress immune responses (38,39). Thus, the immunosuppressive PCs described in prostate cancer (36) may be unique to that disease, as the PCs found in HGSC and other malignancies have properties and associations consistent with a positive role in antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…þ PCs have also been described in autoimmunity, where they serve to exacerbate rather than suppress immune responses (38,39). Thus, the immunosuppressive PCs described in prostate cancer (36) may be unique to that disease, as the PCs found in HGSC and other malignancies have properties and associations consistent with a positive role in antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in CD138+ cells may lead to reduced anti-dsDNA antibody production, because CD138 is expressed in B cell precursors and plasma cells that are responsible for autoantibody production2425. It was reported that the levels of circulating soluble CD138, the expression of CD138 mRNA in peripheral mononuclear cells, and the numbers of plasma cells increased in patients with active SLE compared with normal controls26.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in mechanism may be due to differences in our vaccination model which lacks the inflammation common to the lupus system. In lupus patients, conditions of chronic inflammation produced by myeloid cells leads to plasmablasts are overrepresented in the blood and in peripheral tissues including kidney (17, 18). It would be interesting to repeat these experiments using strong adjuvants or an infection model where inflammation may change the role that myeloid subsets play regulating ASC responses.…”
Section: Discussionmentioning
confidence: 99%